Socio-medical analysis of patients aged 0-6 years reporting to the dentist - Kubić-Filiks, Beata; Rosiak, Joanna; Szalewski, Leszek; Pietryka-Michałowska, Elżbieta; Szymańska, Jolanta (Polish Journal of Public Health, 2016)
Introduction. The results of epidemiological and socio-medical studies of specific age groups in Poland indicate that tooth decay and periodontal diseases still pose a significant health problem. Aim. The aim of the study was the assessment of the reasons for reporting to the dental office and the assessment of oral health in children aged 0-6 years. Material and methods. The study comprised 45 patients in the preschool age (2-6 years old), who for the first time reported in 2015 to the dental office, which offers treatment under the framework of an agreement with the National Health Fund or for a fee. Gender, age, the place of residence and the reason for the reporting to the dentist were analyzed. The place of residence was a village, a town of less than 200 thousand inhabitants or the city of more than 200 thousand inhabitants. The reason for reporting to the dental office was a check-up visit, toothache or loss of filling. Dental condition was assessed by calculating the dmf index. The results were statistically analyzed. Results. Among the surveyed, there were no children younger than 2-year-olds. It was found that the dmf index was ranging in an individual patient from 0 to 20, in half of them the dmf index value was ≤ 7, while in all of the patients the average dmf index was 6.42. The percentage of respondents with dmf=0 was significantly higher among children living in the city than children living in rural areas. Conclusion. It is necessary to intensify educational activities concerning oral health of children, addressed to pregnant women, parents and people from the living environmental of a little child. This applies in particular to promoting early reporting to the first ever, the adaptive visit of a child to the dentist, frequent and regular check-up visits, during which, regardless of the examination, prophylaxis or treatment activities can be carried out if necessary.